Rising income inequality and the relative decline in subjective social status of the working class - Nolan, B; Weisstanner, D (Taylor and Francis, 2022)
The declining ‘subjective social status’ of the low-educated working class has been advanced as a prominent explanation for right-wing populism. The working class has certainly been adversely affected by rising income inequality over the past decades, but we do not actually know if their perceived standing in the social hierarchy has declined correspondingly over time. This article examines trends in subjective social status in two ‘most likely cases’ – Germany and the US – between 1980 and 2018. We find that the subjective social status of the working class has not declined in absolute terms. However, there is evidence for relative status declines for the working class in Germany and substantial within-class heterogeneity in both countries. These findings imply that rising income inequality has a nuanced impact on status perceptions. When assessing the role of subjective social status for political outcomes, longitudinal perspectives that consider both absolute and relative changes seem promising.